Ameliyat sırası basınç yaralanması ve risk faktörlerinin belirlenmesi - İPEK, Büşra (My University, 2022)
This study was planned to determine the risk of intraoperative pressure injury (IPJ) specific to the surgical site and the factors contributing to its occurrence. The research is a descriptive cross-sectionsl design. The study was carried out on 200 patients who underwent surgery in the operating rooms of a private university hospital. Data of the study were obtained through the patient clinical records of the "Sociodemographic and Clinical Characteristics Form" and the "3S Intraoperative Risk Assessment Scale of Pressure Sore, Turkish Form (3S-RTÖ)". Voluntary consent was obtained from the ethics committee, institutions, and participants for the study. 53.5% of the participants were female, average age was 50.26±17.30, and 40% had chronic diseases. Intraoperative pressure injury was seen only as Stage I in 18% of them. The 3S-RTÖ risk score of 36 (18.0%) patients who developed pressure injury (17,64±3,081) was evaluated as higher risk than the 3S-RTÖ risk score of 164 (82.0%) patients who did not develop pressure injury (p=0,004). Intraoperative pressure injury; was more common in female (p=0.013) patients, those over the average age of 57 years (p=0.004), and those with chronic diseases (p=0.035), and with blood pressure changes (hypo/hypertension). The fact that the amount of bleeding of the participants was more than 200 ml, the duration of the operation lasted longer than three hours, and the major surgical intervention were important in the occurrence of intraoperative pressure injury (p=0.001). In determining the risk of intraoperative pressure injury, it is important to know the individual characteristics of the patients as well as the risks specific to the surgery. Intraoperative pressure injury is an important complication that operating room nurses need to detect early and take precautions in patients undergoing major surgery.
Bu çalışma, cerrahi alana özgü ameliyat sırası basınç yaralanması (ASBY) riski ve oluşumuna katkı sağlayan faktörlerin belirlenmesi amacıyla planlandı . Araştırma tanımlayıcı kesitsel bir tasarımdır. Çalışma özel bir Üniversite hastanesinin ameliyathanelerinde cerrahi girişim geçiren 200 hasta üzerinde gerçekleştirildi. Çalışma verileri, "Sosyodemografik ve Klinik Özellikler Formu" ile "3S Ameliyathane Basınç Yarası Risk Tanılama Ölçeği Türkçe Formu (3S-RTÖ)" hasta klinik kayıtları aracılığı ile elde edildi. Çalışma için etik kurul, kurum ve katılımcılardan gönüllü izni alındı. Katılımcıların %53,5'i kadın, yaş ortalaması 50,26±17,30 , %40'ı kronik hastalık sahibiydi. Hastaların sadece %18'inde evre I ameliyat sırası basınç yaralanması görüldü. Basınç yaralanması gelişen 36 (%18,0) hastanın 3S-RTÖ risk puanı (17,64±3,081), basınç yaralanması gelişmeyen 164 (%82,0) hastanın 3S-RTÖ risk puanından (15,55±2,570) daha yüksek riskli olarak değerlendirildi (p=0,001). Ameliyat sırası basınç yaralanması; kadın (p=0,013) hastalarda, 57 yaş ortalaması üzerindekilerde (p=0,004) ve kronik hastalığı olanlarda (p=0,035), kan basıncı değişimi (hipo/hpertansiyon) olanlarda daha çok görüldü. Katılımcıların kanama miktarının 200 ml'den fazla olması, ameliyat süresinin üç saatten uzun sürmesi ve büyük cerrahi girişim geçirmesi ameliyat sırası basınç yaralanması görülmesinde önemliydi (p=0,001). Ameliyat sırası basınç yaralanması riskinin belirlenmesinde hastaların ameliyat sırasına özgü risklerinin bilinmesi kadar bireysel özelliklerinin de bilinmesi önemlidir. Ameliyat sırası basınç yaralanması ameliyathane hemşirelerinin büyük cerrahi girişim geçiren hastalarda erken tanılaması gereken ve önlem alması gereken önemli komplikasyondur.
Keywords: Basınç ülserleri; Pressure ulcer; Cerrahi; Surgery; Perioperatif hemşirelik; Perioperative nursing; Risk faktörleri; Risk factors